Engineering electromagnetics - Hayt, William Hart (McGraw-Hill electrical and electronic engineering series, 1974)
The classic in the field for over four decades has just been updated with new topics, more numerical examples, and drill problems with answers, making independent learning a snap. With an emphasis on fundamentals and problem solving, this superlative text is a must-have for electrical engineers